The Study on The Impact in Policy of Laissez Faire During Scarcities Under Indian Administrative Jurisprudence: A Case Analysis of Water Scarcity in Tamilnadu Under Administrative Regime - SUNDARAM B, LEELESH; A, SREELATHA; V, VISHNU PRIYA; R, GAYATHRI. (The journal of contemporary issues in business and government, 2020)
Concept of Laissez faire is deemed to be the most apt practice under the ambit of administrative jurisprudence, but under the Indian context, the picture is unclear with respect to the impact of the same during scarcities. The scarcity of water in the state of Tamil Nadu has become a burning issue in the current scenario. But as a result of the policy of laissez faire the administrative bodies have not taken a direct step to offer a solution for the problem. Under this kind of a administrative function and psychology a natural ambiguity arises with respect to the impact of laissez faire during scarcities and calamities in the state and a clear picture is required with respect to the administrative mechanism or policy of the government during scarcities and a natural question arises as to functions of administrative bodies during catastrophes and crises. Therefore the study is carried out with an aim to find out the impact of laissez faire policy in scarcities with the help of Tamil Nadu administrative regime. By the virtue of non-probability convenience sampling, existence of an adverse impact of laissez faire in Tamil Nadu water scarcity problem could be framed as the result of the study. The study concludes that policy of laissez faire lacks effectiveness during scarcities and the study recommends that the nature of functioning need to be changed during the times of scarcities and crisis.